2007
DOI: 10.1063/1.2779109
|View full text |Cite
|
Sign up to set email alerts
|

Transverse domain walls in nanoconstrictions

Abstract: The spin structure of domain walls in constrictions down to 30 nm is investigated both experimentally with electron holography and with simulations using a Heisenberg model. Symmetric and asymmetric transverse domain walls for different constriction sizes are observed, consistent with simulations. The experimentally observed asymmetric transverse walls can be further divided into tilted and buckled walls, the latter being an intermediate state just before the vortex nucleation. As the constriction width decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…Furthermore, the ability to control the structure of a domain wall through the geometrical dimensions of the magnetic wire allows the experimental study of fundamental physical properties of these different types of DWs. [9][10][11][12] Although there have been several experimental studies reporting the ability of artificially created constrictions to pin DWs, 10,[13][14][15] and numerous spin-transfer experiments currently use such artificial defects to precisely locate and hold DWs within magnetic nanostructures, 16,17 a complete understanding of how the local DW energy landscape is modified by artificial structural defects is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ability to control the structure of a domain wall through the geometrical dimensions of the magnetic wire allows the experimental study of fundamental physical properties of these different types of DWs. [9][10][11][12] Although there have been several experimental studies reporting the ability of artificially created constrictions to pin DWs, 10,[13][14][15] and numerous spin-transfer experiments currently use such artificial defects to precisely locate and hold DWs within magnetic nanostructures, 16,17 a complete understanding of how the local DW energy landscape is modified by artificial structural defects is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many Py nanostructures of various shapes and sizes have been synthetized using electron beam or UV lithography processes. [1][2][3][4][5][6][7][8][9][10][11][12]15,16 The use of ferromagnetic materials alternative to Py and the development of advanced nanofabrication methods allowing creating magnetic nanostructures of dimensions less than 100 nm are however needed to explore their functionalities and possible applications. In the last years, focused electron beam induced deposition (FEBID) technique has demonstrated a capacity to produce high quality nanostructures based on multiple materials.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] These innovative ideas and promising applications have motivated extensive developments of ferromagnetic nanostructures in which DW can be "easily" created and driven either by external magnetic fields and/or spin-polarized currents. [6][7][8][9][10][11][12] DW in magnetic nanostructures have therefore become a major topic for the research community in the field of Nanomagnetism. The specific DW configuration is the result of the balance between the magnetostatic energy, the magnetocrystalline anisotropy, and the exchange coupling.…”
mentioning
confidence: 99%
“…For the imaging of the domain wall spin configurations in rings of other materials, previous work has employed electron holography [21] or Lorentz microscopy, which require that the samples are fabricated on delicate membranes for the transmission measurements [10], photo-emission electron microscopy [17,18,31], which is mainly available at large-scale facilities and can be limited in its resolution, or magnetic force microscopy (MFM) [9,[32][33][34], which can modify the spin configuration of the sample and is however sensitive only to the stray magnetic field from a sample and therefore harder to relate directly to the spin structures obtained from simulations. Therefore, in this paper we chose the imaging technique SEMPA [26], which is a powerful lab-based method with an excellent spatial resolution of less than 20 nm and which can provide quantitative direct information concerning the spin configurations [35].…”
Section: Experimental and Numericsmentioning
confidence: 99%
“…While many studies just consider the two types of domain wall mentioned above, it has been predicted [13] and experimentally confirmed [21] that the transverse domain wall can occur in both symmetric and asymmetric configurations, which are expected to have different properties. For example, it has recently been revealed that the symmetry of the transverse domain wall is important in determining the depinning process from domain wall traps [22] and wire kinks [23].…”
Section: Introductionmentioning
confidence: 99%